2018
DOI: 10.13048/jkm.18040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GHX02 on Chronic Obstructive Pulmonary Disease Mouse Model

Abstract: Objectives: Chronic obstructive pulmonary disease (COPD) is characterized by chronic inflammation and irreversible airflow. This study aimed to evaluate the effects of GHX02 in a COPD-induced mouse model. Methods: The COPD mouse model was established by exposure to cigarette smoke extract and lipopolysaccharide which were administered by intratracheal injection three times with a 7 day interval. GHX02 (100, 200, 400 mg/kg) and all other drugs were orally administrated for 14 days from Day 7 to Day 21. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Furthermore, GHX02 suppressed PM 10 D-induced inflammatory symptoms in the lungs, such as increased alveolar wall thickness, cytokine release, and collagen fiber accumulation ( Yang et al, 2020 ). In addition, we observed that GHX02 efficiently inhibited airway inflammation by inhibiting the expression of proinflammatory cytokines and the migration of inflammatory cells in a COPD-induced mouse model ( Yang et al, 2018 ). In a subsequent study investigating the mechanism, the GHX02 herbal formula protects against TNF-α-induced inflammation in human bronchial epithelial cells by blocking NF-κB and activating the Nrf-2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GHX02 suppressed PM 10 D-induced inflammatory symptoms in the lungs, such as increased alveolar wall thickness, cytokine release, and collagen fiber accumulation ( Yang et al, 2020 ). In addition, we observed that GHX02 efficiently inhibited airway inflammation by inhibiting the expression of proinflammatory cytokines and the migration of inflammatory cells in a COPD-induced mouse model ( Yang et al, 2018 ). In a subsequent study investigating the mechanism, the GHX02 herbal formula protects against TNF-α-induced inflammation in human bronchial epithelial cells by blocking NF-κB and activating the Nrf-2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Scutellariae radix has also been reported to inhibit the production of several inflammatory cytokines ( Kim et al, 2015 ) and have antioxidant effects ( Guo et al, 2013 ). Moreover, a series of preclinical studies showed that GHX02 reduced airway inflammation, sputum production, cough, suppressed PM10D-induced inflammatory symptoms in the lung ( Yang et al, 2020 ), and had an anti-COPD effect ( Yang et al, 2018 ). Additionally, the safety of GHX02 has been verified in the assessment of 4-weeks repeated-dose oral toxicity and genotoxicity ( Ji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…질환이다 1 6 에 따라 살펴보면 풍한형(風寒 型)의 소청룡탕 7 , 폐열형(肺熱型)의 과루행련환 유 래 GHX02 8 , 담탁형(痰濁型)의 사간탕 유래 SGX01 9 , 폐허형(肺虛型)의 감길탕 유래 GGX 10 , 신음허형 (腎陰虛型)의 청상보하탕 유래 PM014 11 등이 있었 으나 COPD에 병발하는 근감소에 대한 영향을 동 시에 평가한 연구는 찾기 어려웠다. 쌍화탕(雙和湯)은 ≪동의보감(東醫寶鑑)≫ 12 에서 정신과 신체가 피로하고 기혈이 모두 손상되었을 때 사용하는 것으로 기재된 처방으로 사물탕(四物 湯)과 황기건중탕(黃耆建中湯)의 합방으로 구성되 어 있으며 13 , 항피로 14 , 면역활성화 15 에 대한 효능 연 구와 운동수행능력 16 , 만성피로 17 기기는 열탕추출기(Daewoong, Korea), rotary vacuum evaporator(Buchi, Switzerland), freeze dryer (EYELA, Japan), CO2 incubator(Forma Scientific, USA), micro-pipet(Gilson, France), clean bench(Vision Scientific, Korea), autoclave(Sanyo, Japan), water bath(Vision scientific, Korea), Biosystem XA(Buxco Research System, USA), vortex mixer(Vision scientific, Korea), spectrophotometer(Shimazue, Japan), thermocycler system(MWG Biotech, Germany), deep-freezer(Sanyo, Japan), centrifuge(Sigma, USA), homogenizer(OMNI, USA), plate shaker(Lab-Line, USA), ELISA reader (Molecular Devices, USA), ice-maker(Vision scientific, Korea) 및 chemical balance(Cas, Korea) 등을 사 용하였다.…”
unclassified